La solidarité écologique appliquée au système océanique : quelles perspectives juridiques ? - Justine Réveillas (VertigO)
Negotiations within the United Nations on the conservation and sustainable use of marine biodiversity beyond national jurisdictions provide an ideal timeliness to propose a new legal principle to transform the environmental governance of the areas beyond national jurisdictions (ABNJ). As part of a collective work on the definition of a principle of ecological solidarity with a universal vocation, this contribution is an opportunity to deepen the reflections through a normative application of ecological solidarity to the Ocean system. Thanks to scientific progress, the natural sciences describe the Ocean system as a model of fact ecological solidarity, marked by the interdependence of ecosystems and living beings. However, this ecological solidarity is today largely ignored by the international law of the sea. This non-consideration of the law in the face of the ecological reality of the Ocean system invites us to rethink the modalities of governance in the light of ecological solidarity and to propose a principle of ecological solidarity to protect marine biodiversity located beyond national jurisdictions.